Beyond Volume: Hospital-Based Healthcare Technology for Better Outcomes in Cerebrovascular Surgical Patients Diagnosed With Ischemic Stroke: A Population-Based Nationwide Cohort Study From 2002 to 2013. Issue 11 (March 2016) - Kim, Jae-Hyun; Park, Eun-Cheol; Lee, Sang Gyu; Lee, Tae-Hyun; Jang, Sung-In
Abstract : Abstract: We examined whether the level of hospital-based healthcare technology was related to the 30-day postoperative mortality rates, after adjusting for hospital volume, of ischemic stroke patients who underwent a cerebrovascular surgical procedure. Using the National Health Insurance Service-Cohort Sample Database, we reviewed records from 2002 to 2013 for data on patients with ischemic stroke who underwent cerebrovascular surgical procedures. Statistical analysis was performed using Cox proportional hazard models to test our hypothesis. A total of 798 subjects were included in our study. After adjusting for hospital volume of cerebrovascular surgical procedures as well as all for other potential confounders, the hazard ratio (HR) of 30-day mortality in low healthcare technology hospitals as compared to high healthcare technology hospitals was 2.583 ( P < 0.001). We also found that, although the HR of 30-day mortality in low healthcare technology hospitals with high volume as compared to high healthcare technology hospitals with high volume was the highest (10.014, P < 0.0001), cerebrovascular surgical procedure patients treated in low healthcare technology hospitals had the highest 30-day mortality rate, irrespective of hospital volume. Although results of our study provide scientific evidence for a hospital volume/30-day mortality rate relationship in ischemic stroke patients who underwent cerebrovascular surgical procedures, our results also suggest that the level of hospital-based healthcare technology is associated with mortality rates independent of hospital volume. Given these results, further research into what components of hospital-based healthcare technology significantly impact mortality is warranted.